2020
DOI: 10.1177/8755293020926183
|View full text |Cite
|
Sign up to set email alerts
|

Observed damage in public school buildings during the 2017 Mexico earthquakes

Abstract: In September 2017, two major earthquakes struck south and central Mexico. These earthquakes produced widespread damage in public and private school infrastructure. In Mexico, all school buildings are classified as essential infrastructure and are expected to attain an immediate occupancy performance level after major earthquakes. However, there is a large variation in the quality of the design and construction practices of these buildings due to age of construction, material quality and availability, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 1 publication
0
25
0
Order By: Relevance
“…The impact of the needs of innovative educational environments and methods (new teaching techniques and models) on school infrastructure should be assessed and included in the design and construction requirements. e. Guide for construction and construction inspection of school campuses: as it was mentioned in the companion article (Alcocer et al 2020), the substandard performance was observed because of inadequate inspection of buildings during construction; the ''short column'' effect is a prime example. To reverse this situation, a guide and outreach efforts on school inspection during construction is proposed.…”
Section: Policy Recommendationsmentioning
confidence: 99%
See 4 more Smart Citations
“…The impact of the needs of innovative educational environments and methods (new teaching techniques and models) on school infrastructure should be assessed and included in the design and construction requirements. e. Guide for construction and construction inspection of school campuses: as it was mentioned in the companion article (Alcocer et al 2020), the substandard performance was observed because of inadequate inspection of buildings during construction; the ''short column'' effect is a prime example. To reverse this situation, a guide and outreach efforts on school inspection during construction is proposed.…”
Section: Policy Recommendationsmentioning
confidence: 99%
“…Requirements and specifications for most common construction materials, systems, methods, and procedures should be included. f. Guide for maintenance and conservation of school buildings: as it was mentioned in Alcocer et al (2020), school buildings with adequate maintenance exhibited superior seismic performance compared with those with poor maintenance. Moreover, buildings with modifications to structural elements and/or layout without proper technical review and approval also showed more damage.…”
Section: Policy Recommendationsmentioning
confidence: 99%
See 3 more Smart Citations